2020
DOI: 10.1073/pnas.2005794117
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell lysate-loaded immunostimulatory spherical nucleic acids as therapeutics for triple-negative breast cancer

Abstract: Highly heterogenous cancers, such as triple-negative breast cancer (TNBC), remain challenging immunotherapeutic targets. Herein, we describe the synthesis and evaluation of immunotherapeutic liposomal spherical nucleic acids (SNAs) for TNBC therapy. The SNAs comprise immunostimulatory oligonucleotides (CpG-1826) as adjuvants and encapsulate lysates derived from TNBC cell lines as antigens. The resulting nanostructures (Lys-SNAs) enhance the codelivery of adjuvant and antigen to immune cells when compared to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 74 publications
2
67
1
Order By: Relevance
“…In addition, whole-tumor lysates can be delivered within liposomal spherical nucleic acids (SNAs) composed of adjuvants. For example, a complex consisting of murine triple-negative breast-cancer cell lysates encapsulated with SNAs consisting of CpG on the surface induced tumor rejection and in vitro activation of BM-DCs ( 84 ).…”
Section: Delivery Of Antigensmentioning
confidence: 99%
“…In addition, whole-tumor lysates can be delivered within liposomal spherical nucleic acids (SNAs) composed of adjuvants. For example, a complex consisting of murine triple-negative breast-cancer cell lysates encapsulated with SNAs consisting of CpG on the surface induced tumor rejection and in vitro activation of BM-DCs ( 84 ).…”
Section: Delivery Of Antigensmentioning
confidence: 99%
“… 10 , 28 For cancers without identified TAAs, L-SNAs have been used to encapsulate tumor cell lysates as potent antigen sources. 9 In mouse models of triple-negative breast cancer (TNBC), it has been found that the process by which lysates are generated prior to L-SNA incorporation changes the available antigen pool, which impacts the immunotherapeutic potency of the construct.…”
mentioning
confidence: 99%
“…Nanoparticles have been used to develop new vaccine delivery mechanisms and mimic the immune system attack on cancer cells. [ 209–212 ] These nanoparticles can be designed to deliver the payload to specific tissues and regions in the body to treat targeted areas. For example, layer‐by‐layer assembly of lipids can encapsulate antigen and can also be functionalized with different physiochemical and biological properties.…”
Section: Future Outlook: Application Of Cofs In Immune Engineeringmentioning
confidence: 99%